2011
DOI: 10.1074/jbc.m110.203448
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Up-regulation of Nedd4 Family Interacting Protein 1 (Ndfip1) using Low Levels of Bioactive Cobalt Complexes

Abstract: The delivery of metal ions using cell membrane-permeable metal complexes represents a method for activating cellular pathways. Here, we report the synthesis and characterization of new [ Transition metals are essential for many important chemical processes in biological systems. Most of these metal-related processes occur by interactions with nucleic acids and proteins. Within the cell, metal ions can stabilize, destabilize, or modulate DNA and proteins by introducing conformational changes and by creating cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The X‐ray structure also showed that the complex had recrystallised as a single enantiomer. As expected, the metal ion has a distorted octahedral environment, and the Co–N1 [1.903(7) Å] and Co–O1 [1.865(5) Å] bond lengths are similar to those found in a comparable Co III (L)acac complex with a simple Schiff base ligand …”
Section: Resultssupporting
confidence: 71%
“…The X‐ray structure also showed that the complex had recrystallised as a single enantiomer. As expected, the metal ion has a distorted octahedral environment, and the Co–N1 [1.903(7) Å] and Co–O1 [1.865(5) Å] bond lengths are similar to those found in a comparable Co III (L)acac complex with a simple Schiff base ligand …”
Section: Resultssupporting
confidence: 71%
“…Ndfip1 can be upregulated in response to extracellular stress such as hypoxia or metal toxicity [4], [5], and this activation results in the regulation of a number of critical proteins such as DMT1. Previously we have observed that in an environment where metal concentrations are elevated, Ndfip1 is upregulated by a mechanism that does not require either HSP70 or HIF-1α response [28], and resulted in the binding and degradation of DMT1 [5]. It should be noted that DMT1 abundance can also be regulated transcriptionally and differential expression of DMT1 isoforms having been observed due to iron exposure [10], hypoxia [29] and NFκB activation [30].…”
Section: Discussionmentioning
confidence: 98%
“…Unlike the previously studied inert 3 d 8 nickel(II) ion, cobalt(III) is a redox-active species capable of being reduced to cobalt(II) within the reducing cellular environment by available reductants. This reduction has been demonstrated individually by several groups [12,13] and utilized for release of alkylating agents such as nitrogen mustards. The redox potential for the cytosolic environment is reported to be around −0.3 V vs. NHE by Østegaard [32].…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor activity of cobalt species is fairly understudied, [10] but activity against prostate cancer has been recently demonstrated by McNail et al for bivalent cobalt. [11] On the other hand, Teicher, Ware, Hambley, [12] and more recently Donelly [13] have taken advantage of bioreductive activation of its trivalent counterpart for the treatment of hypoxic tumors. In this case, intracellular redox conversion of Co(III) into Co(II) releases alkylating mustards.…”
Section: Introductionmentioning
confidence: 99%